The Effect of Counseling With Dietary Journal on Knowledge, Attitude, And Compliance of Renal Failure Patients on Haemodialysis Therapy - Marbun, Rosmida Magdalena; Rabbani, Fairuz Dhia; Maya, Candra; Karina, Sadiah Multi (Politeknik Kesehatan Kemenkes Jakarta II, 2023)
Chronic kidney disease (CKD) is a form of renal failure for 3 consecutive months that can be treated with hemodialysis. CKD patients need to undergo diet according to their kidney condition to prevent complications. On Riskesdas 2018, the prevalence of CKD reached 3.8 percent for population aged ≥15 years. The study aimed to determine the effect of nutritional counseling with dietary journal on the knowledge, attitudes, and dietary compliance of CKD patients who were undergoing hemodialysis at PGI Cikini Hospital. The study used a one-group pre and post-test design with 39 samples. Nutrition counseling was carried out using dietary journal twice. Knowledge and attitudes of samples were collected by asking samples to fill out questionnaire before and 1 week after nutrition counselings. Dietary compliances were collected from energy intake, macro and micronutrients, and IDWG values. The results showed that there were increases in the number of samples with adequate and good knowledge levels, positive attitudes, and in the compliant group to 84.6 percent; 94.9 percent; and 69.3 percent, respectively. Bivariate analysis showed that there were significant differences in the level of knowledge and compliance of CKD patients underwent hemodialysis at RSI PGI Cikini after nutrition counseling with a dietary journal. However, nutrition counseling has no effect on patients’ attitudes towards hemodialysis diet. It was concluded that nutritional counseling with a dietary journal affected the knowledge and dietary compliance of CKD patients underwent hemodialysis at PGI Cikini Hospital. Dietary journal can be used as a tool to monitor patient’s dietary compliance. Keywords: nutrition counseling, dietary journal, CKD